The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4103/2230-8229.181012
|View full text |Cite
|
Sign up to set email alerts
|

Preconception care in Saudi women with diabetes mellitus

Abstract: Background:The rate of preexisting diabetes mellitus (DM) in Saudi Arabia is one of the highest in the world. The role of preconception care (PCC) is well-established as a means of improving pregnancy outcomes in DM.Objectives:To assess the rate of preconception counseling, the level of PCC knowledge, and the rate of unplanned pregnancies in Saudi women with DM.Materials and Methods:A cross-sectional study was conducted among 355 Saudi women aged 18–49 years with self-reported DM. The study questionnaire conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
19
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 30 publications
15
19
7
Order By: Relevance
“…However, it is lower than the findings from Saudi Arabia (57.2%), Jordan (85%), and in USA among low income Mexican American group (76%) (18)(19)(20). The low knowledge level in this study might be due to the relative low media coverage in Ethiopia concerning PCC, which showed there is a need to broaden media coverage in the country.…”
Section: Discussioncontrasting
confidence: 82%
“…However, it is lower than the findings from Saudi Arabia (57.2%), Jordan (85%), and in USA among low income Mexican American group (76%) (18)(19)(20). The low knowledge level in this study might be due to the relative low media coverage in Ethiopia concerning PCC, which showed there is a need to broaden media coverage in the country.…”
Section: Discussioncontrasting
confidence: 82%
“…The highest knowledge in this study might be due to the fact that there were varied in time and large and representative sample size, which make the study comprehensive. However, it is significantly lower than the findings from Saudi Arabia (37.9%), Jordan (85%) [19, 20], Egyptian (76%) and Arabian (51%) mothers [21]. The low knowledge level in this study might be due to the relative low media coverage in Ethiopia, which showed there is a need to broaden media coverage in the country.…”
Section: Discussioncontrasting
confidence: 75%
“…Knowledge was measured based on respondent's correct response to preconception care knowledge questions. Those respondents who correctly respond to 50% or more of the preconception care knowledge questions were considered to have good knowledge and those who scored<50% were considered as having poor knowledge (11,12). The data was coded and entered into Epi-data version 4.2.0 then exported to statistical package for social science (SPSS) version 25.…”
Section: Methodsmentioning
confidence: 99%